Bibliographic analysis of acarological papers published in Zootaxa from 2001 to 2005, with a catalogue of described new taxa - Fan, Qing-Hai (Zootaxa, 2006)
Bibliographies and catalogues of scientific literature play important roles in taxonomy and enable taxonomists gathering and acquiring information quickly and easily. In order to provide an overview of the progress of systematic acarology, the author studied the papers published in Zootaxa from 2001 to 2005 and presented a bibliographical analysis of these papers and a list of the described new taxa including 16 genera and 185 species.